Zur Reformbedürftigkeit der Verkehrsunfallflucht (§ 142 StGB) - Kubatta, Ziva (Universitätsverlag Göttingen, 2008)
The investigation deals with the accident flight Paragraph § 142 of the German StGB (criminal code). It examines the questions of "if" and the "how" of reform, this means the practical embodiment in detail.